Synergies and Dilemmas in Asset and Liability Investment Strategies: A Multidisciplinary Analysis in the Context of the Efficient Market Hypothesis, Anomalies and Portfolio Design - Norman SCHERER (Communications of International Proceedings, 2023)
This paper comprehensively examines the dichotomy between active and passive investment strategies in the context of the efficient market hypothesis. While the efficient market hypothesis implies that all available information is contained in the market price and thus excess returns are systematically unattainable, empirical data and real-world examples show that there are investors like Warren Buffet who can beat the market in the long run. The article also highlights the role of anomalies and rationality breaks that give active strategies room for excess returns, as well as the challenges that active portfolio managers face in the form of transaction costs and competitive pressures. The core-satellite approach is presented as a bridge between the two investment styles, allowing for a flexible combination of active and passive elements. The paper argues that no approach is universally superior; effectiveness depends on various factors such as market efficiency, volatility, and the specific skills of the investor. It also introduces ethical and organizational considerations into the investment process, emphasises the need for continuous monitoring and transparency. Finally, the paper discusses the importance of flexibly adjusting the investment strategy in response to market conditions and presents an integrated perspective that combines modern portfolio theory and behavioral finance.
Keywords: Active investment strategies; passive investment strategies; efficient market hypothesis; excess return